Molecular characterization and experimental infection of infectious spleen and kidney necrosis virus from ornamental fish in Peninsular Malaysia - Subramaniam, Kuttichantran (2014)
Infectious spleen and kidney necrosis virus (ISKNV) has been reported in the ornamental fish and this virus belongs to the genus Megalocytivirus. Even though this virus have been reported in many countries such as Japan, China, Korea, Taiwan,Thailand and Singapore, the impact and extent of this disease is unknown hitherto at Malaysia. This is due to lack of knowledge on the host range, geographical distribution and the differences between strains if any. Hence to elucidate this gap of knowledge,‘gold standard’ OIE reference polymerase chain reaction (PCR) assay was utilized to detect the presence of ISKNV in farmed ornamental fish from Peninsular Malaysia. A total of 210 ornamental fish samples were collected. Of these, ISKNV was detected in 36 ornamental fish samples and they were asymptomatic. Three restriction enzymes analyses showed that the fish were infected by identical strains of same virus species within Megalocytivirus genus. Major capsid protein (MCP) gene of 10 ISKNV strains were sequenced and compared with 9 other reference nucleotide sequences acquired from GenBank. Sequence analysis of MCP gene showed that all strains detected in this study were closely related to the reference ISKNV with nucleotide sequence homology ranging from 99.8 % to 100 %. In addition, phylogenetic analysis of MCP gene revealed that the reference ISKNV which was obtained from GenBank and all other strains that were detected in this study were included in genotype 1. Since all the infected fish appeared healthy, there was a concern over possible transmission of asymptomatic ISKNV infection in freshwater ornamental fish species. To clarify this, an experimental trial was conducted to investigate the possible transmission of ISKNV infection in ram cichlid by cohabitation. The ISKNV is able to transmit from treated fish to cohabited fish within first week of trial and the infected fish were asymptomatic. The presence of ISKNV in the experimentally infected fish was confirmed by PCR assay and histopathology. The ISKNV carrier pose serious risk to the Malaysian aquaculture industry as this virus can spread without any sign of disease. The inclusion body-bearing cells (IBCs) which are pathognomonic for Megalocytivirus infection were present in the liver and spleen. In addition, other histopathological changes such as accumulation of inflammatory cells in splenic pulp and well defined melano-macrophage centers varied from yellow-brown to black deposition of melanin were noted in the spleen. Visual inspection for clinical signs is not suitable to monitor ISKNV infection as this disease can be asymptomatic in fish. Hence, a highly specific and simple loop-mediated isothermal amplification (LAMP) method was developed in this study for the detection of ISKNV. A set of four primers was designed based on the ISKNV MCP gene sequences. The optimum temperature and time for the LAMP assay were 65 ºC and 60 min, respectively. This assay does not require any sophisticated equipments and allows the investigators to carry out the diagnostic test at farm. Compared to other molecular diagnostic methods such as PCR and qPCR, the reaction time for LAMP assay is shorter and gives instant result without the need of any lengthy post reaction procedures. Accurate identification of the pathogens using highly specific diagnostic tool is paramount to control the spread of infectious diseases. One of the advantages of present LAMP assay was its specificity towards ISKNV. The primers were specific for ISKNV and there was no cross amplification with red sea bream iridovirus (RSIV), white spot syndrome virus (WSSV), Aeromonas hydrophila or Vibrio parahaemolyticus. The detection limit of LAMP assay was 20 fg. Diluted acridine orange was used to detect the presence of amplified product and this novel step turns the amplified LAMP product into yellow indicating positive reaction and remains orange on negative reaction. In addition, usage of acridine orange in LAMP product gives clear qualitative result which can be visualized without the aid of special lighting or agarose gel electrophoresis. In summary, the extent of ISKNV infection in farmed ornamental fish which includes information on the host range and geographical distribution in Peninsular Malaysia has been revealed in this study. This baseline information is essential to mitigate the spread of this disease. Present study also confirms the transmission of the asymptomatic ISKNV infection in ram cichlid by cohabitation. There were no previous reports on the transmission of asymptomatic ISKNV by cohabitation. The current LAMP technique for the detection of ISKNV is a simple, specific and inexpensive diagnostic tool under laboratory conditions and also in the field.